Introducing contemplative studies - Komjathy, Louis (Wiley Blackwell, 2018)
Contemplative studies -- Contemplative practice -- Contemplative experience -- Contemplative traditions -- Contemplative pedagogy -- Interpretive approaches -- Current trends -- Future prospects